PEMBELAJARAN MENULIS ESAI DALAM DISERTASI: KAJIAN METAKOGNITIF - Teguh Budiharso (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2018)
Four dissertations on writing subject are analyzed in this study implementing metacognitive analyses.  The analysis focused on the overall aspects of how research procedures are employed and how the findings of those dissertations are modified for the purpose of a new research on similar concerns.  The study reveals that prospective research topics in writing are available.  Both approaches and topics of writing are offered from which research designs vary.  Quantitative approaches using experimental study may be focused on the testing of teaching methods in writing, writing strategies, the writing process, and techniques of writing.  Rhetoric and linguistics aspects of writing are topics from which researchers can develop with various objectives.  Specifically, assessment on writing is a prospective field that is recently required in relation to the performance assessment. In addition, developing teaching materials on the writing of which Research and Development (R&D) design is applicable is also demanding.